The Cambridge Companion to Byron - Bone, Drummond (Cambridge : Cambridge University Press, 2023)
"Deeply informed and appealingly written, this revised and updated second edition gives fresh life to the enthralling sexual, poetic and political contradictions that make Byron the first literary celebrity. An authoritative source for students, this companion also points to emerging new areas of research"--
Keywords: English Poetry -- History and Criticism